Gilberto Conde, Turquía, Siria e Iraq: entre amistad y geopolítica, México, El Colegio de México, 2013, 192 pp. - Chuaqui, Rubén (Estudios de Asia y África, 2014)
Gilberto Conde, Turquía, Siria e Iraq: entre amistad y geopolítica, México, El Colegio de México, 2013, 192 pp.